Targeting TBP-Associated Factors in Ovarian Cancer - Ribeiro, Jennifer R.; Lovasco, Lindsay A.; Vanderhyden, Barbara C.; Freiman, Richard N. (Frontiers in Oncology, 2014)
As ovarian tumors progress, they undergo a process of dedifferentiation, allowing adaptive changes in growth and morphology that promote metastasis and chemoresistance. Herein, we outline a hypothesis that TATA-box binding protein (TBP) associated factors (TAFs), which compose the RNA Polymerase II initiation factor, TFIID, contribute to regulation of dedifferentiation states in ovarian cancer. Numerous studies demonstrate that TAFs regulate differentiation and proliferation states; their expression is typically high in pluripotent cells and reduced upon differentiation. Strikingly, TAF2 exhibits copy number increases or mRNA overexpression in 73% of high grade serous ovarian cancers (HGSC). At the biochemical level, TAF2 directs TFIID to TATA-less promoters by contact with an Initiator element, which may lead to the deregulation of the transcriptional output of these tumor cells. TAF4, which is altered in 66% of HGSC, is crucial for the stability of the TFIID complex and helps drive dedifferentiation of mouse embryonic fibroblasts to induced pluripotent stem cells. Its ovary-enriched paralog, TAF4B, is altered in 26% of HGSC. Here, we show that Taf4b mRNA correlates with Cyclin D2 mRNA expression in human granulosa cell tumors. TAF4B may also contribute to regulation of tumor microenvironment due to its estrogen-responsiveness and ability to act as a cofactor for NFκB. Conversely, TAF9, a cofactor for p53 in regulating apoptosis, may act as a tumor suppressor in ovarian cancer, since it is downregulated or deleted in 98% of HGSC. We conclude that a greater understanding of mechanisms of transcriptional regulation that execute signals from oncogenic signaling cascades is needed in order to expand our understanding of the etiology and progression of ovarian cancer, and most importantly to identify novel targets for therapeutic intervention.